High inflation: resource misallocations and growth effects - Tomassi, Mariano (Estudios de Economía, 2016)
High inflation disrupts the organization of markets. This paper relates those “Industrial Organization” effects of inflation to the poor growth performance of high-inflation economies, in the context of a Schumpeterian growth model.